SAE Technical Paper Series 2016
DOI: 10.4271/2016-32-0085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Turbocharger Speed to Estimate the Cylinder-to-Cylinder Injection Variations - Part 2 - Frequency Domain Analysis

Abstract: For the development of a very high efficiency engine, the continuous monitoring of the engine operating conditions is needed. Moreover, the early detection of engine faults is fundamental in order to take appropriate corrective actions and avoid malfunctioning and failures. The in-cylinder pressure is the most direct parameter associated to the engine thermodynamic cycle. The cost and the intrusiveness of the dynamic pressure sensor and the harsh operating condition that limits its life-time, make the direct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The reliability of the acceleration methodology for the injector performance monitoring is, however, limited by the engine speed. In previous studies [30,31], it was shown in fact that at high engine rotational speeds (3000 rpm and above), the correlation between the TCAF parameter and the injected fuel in one of the cylinders is no longer stable and exploitable, due to the following reasons:  at high engine rotational speeds, the scavenging phase (if present) managed by the valve overlap makes the pressure wave coming from the inlet duct (i.e., from the compressor) affect the pressure at the turbine inlet and the instantaneous TC speed;  high engine speeds are connected to strong pressure pulsations, and consequently to instantaneous TC speed oscillations, characterized by very high frequency, as testified by Eq. 3, where is the number of cylinders, N is the average engine speed and T is the number of strokes of the engine.…”
Section: Technique Based On Tc Accelerationmentioning
confidence: 94%
See 4 more Smart Citations
“…The reliability of the acceleration methodology for the injector performance monitoring is, however, limited by the engine speed. In previous studies [30,31], it was shown in fact that at high engine rotational speeds (3000 rpm and above), the correlation between the TCAF parameter and the injected fuel in one of the cylinders is no longer stable and exploitable, due to the following reasons:  at high engine rotational speeds, the scavenging phase (if present) managed by the valve overlap makes the pressure wave coming from the inlet duct (i.e., from the compressor) affect the pressure at the turbine inlet and the instantaneous TC speed;  high engine speeds are connected to strong pressure pulsations, and consequently to instantaneous TC speed oscillations, characterized by very high frequency, as testified by Eq. 3, where is the number of cylinders, N is the average engine speed and T is the number of strokes of the engine.…”
Section: Technique Based On Tc Accelerationmentioning
confidence: 94%
“…The consideration above is true as long as the engine speed is kept constant. The coefficient of the linear proportionality does change, however, by varying the engine rotational speed, as discussed in [31]. Conversely, it is indeed true that the sensitivity on the F4 module grows by reducing the engine speed.…”
Section: Frequency Content-based Monitoring Techniquementioning
confidence: 95%
See 3 more Smart Citations